고분자전해질연료전지를 위한 그래핀 기반 PtM 촉매들의 산소환원반응성 연구 - 양종원; 최장군; 조한익; 박종찬; 권용재 (한국수소및신에너지학회, 2014)
In this research, we investigate electrical performance and electrochemical properties of graphenesupported Pt (Pt/G) and PtM (M = Ni and Y) alloy catalysts (PtM/Gs) that are synthesized by modified polyolmethod. With the PtM/Gs that are adopted for oxygen reduction reaction (ORR) as cathode of proton exchangemembrane fuel cells (PEMFCs), their catalytic activity and ORR performance and electrical performance areestimated and compared with one another. Their particle size, particle distribution and electrochemically activesurface (EAS) area are measured by TEM and cyclic voltammetry (CV), respectively. On the other hand, regardingORR activity and electrical performance of the catalysts, (i) linear sweeping voltammetry by rotating disk electrodeand rotating ring-disk electrode and (ii) PEMFC single cell tests are used. The TEM and CV measurementsdemonstrate particle size and EAS of PtM/Gs are compatible with those of Pt/G. In case of PtNi/G, its half-wavepotential, kinetic current density, transferred electron number per oxygen molecule and H2O2 production % areexcellent. Based on data obtained by half-cell test, when PEMFC singlecell tests are carried out, current densitymeasured at 0.6V and maximum power density of the PEMFC single cell employing PtNi/G are better than thoseemploying Pt/G. Conclusively, PtNi/Gs synthesized by modified polyol shows better ORR catalytic activity andPEMFC performance than other catalysts.